2014
DOI: 10.1007/s12013-014-0326-5
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin-Sealant-Delivered Cisplatin Chemotherapy Versus Cisplatin Hyperthermic Intraperitoneal Perfusion Chemotherapy for Locally Advanced Gastric Cancer Without Peritoneal Metastases: A Randomized Phase-II Clinical Trial with a 40-Month Follow-up

Abstract: A new intraoperative cisplatin administration method for patients with locally advanced gastric cancer (AGC) and without peritoneal metastasis, fibrin-sealant-delivered cisplatin chemotherapy, was reported, and its safety, pharmacokinetics, and efficacy were compared with cisplatin hyperthermic intraperitoneal perfusion chemotherapy. Forty-two AGC patients were randomly divided into 2 groups: fibrin-sealant-delivered cisplatin chemotherapy (FS) (n = 21) and cisplatin hyperthermic intraperitoneal perfusion chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…The flow diagram in Figure 1 details the selection process. We divided studies into two groups of analysis: treatment of AGC without carcinomatosis (nine RCTs(6, 13–20) and nine NRCTs(6, 2330)) and treatment of GCPC (two RCTs(21, 22) and twelve NRCTs(2426, 2836)). Six authors(2426, 2830) of NRCTs reported in the same article both categories with separate analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The flow diagram in Figure 1 details the selection process. We divided studies into two groups of analysis: treatment of AGC without carcinomatosis (nine RCTs(6, 13–20) and nine NRCTs(6, 2330)) and treatment of GCPC (two RCTs(21, 22) and twelve NRCTs(2426, 2836)). Six authors(2426, 2830) of NRCTs reported in the same article both categories with separate analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In the analysis of AGC without carcinomatosis, we included a total of 1810 patients, 731 undergoing gastrectomy+HIPEC and 1079 standard gastrectomy alone. The nine RCTs(6, 13–20) contributed 970 cases, 404 of them allocated in the HIPEC group. In the GCPC analysis, we included a total of 620 patients, 289 undergoing CRS+HIPEC, while 331 patients served as control cases (244 received cytoreduction surgery and 87 systemic chemotherapy).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Cui et al found that neoadjuvant chemotherapy along with postoperative IP perfusion chemotherapy with hyperthermia achieved a better progression-free survival (33 vs. 26 months), and overall survival (OS) (36 vs. 27 months) than neoadjuvant chemotherapy alone [15]. In contrast, a study by Huang et al found that adjuvant IP chemotherapy with hyperthermia did not prolong OS (29.1 vs. 35.9 months) compared with chemotherapy alone [16]. A recently published study showed that in ovarian cancer the addition of HIPEC to interval cytoreductive surgery resulted in longer recurrence-free survival and OS than surgery alone and had no higher rates of adverse effects [17].…”
Section: Discussionmentioning
confidence: 99%
“…However, the treatment effect of IPC in carcinomatosis of gastric origin remains disappointing and inconclusive. Several trials have indicated that IPC may increase survival rate in advanced gastric cancer [ 9 – 15 ], while the results of another trial showed adverse effects on survival rate [ 16 ]. Furthermore, most relevant trials have suggested that IPC has no significant effect on survival rate [ 17 31 ].…”
Section: Introductionmentioning
confidence: 99%